Evaluation on key node issues in constructing community resilience to cope with public health emergencies in China - Xin ZHANG; Wen-jing ZHOU; Jiu-rui ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo evaluate key node issues in the process of community resilience construction to deal with public health emergencies in China and to provide a reference for the construction and improvement of community resilience. MethodsA list of problems in the construction of community resilience in response to public health emergencies was determined after literature studies and professional group discussions. The severity and the urgency of intervention for each of the problems were assessed through a consultation among 40 senior professionals engaged in emergency response or community management. Technique for order performance by similarity to ideal solution (TOPSIS) method was adopted to rank the importance of the problems. ResultsFor the expert consultation, the positive coefficient was 95.0% and the authority coefficient was 0.774; and the coordination coefficients were 0.387 and 0.428 for the experts' scores of evaluation on the severity and intervention urgency of the 16 items in the problem list of community resilience construction, indicating significant coordination of the experts' evaluation (both P < 0.05). The results of the TOPSIS analysis revealed that the five key node issues in the construction of community resilience include: the absence of the multi-agent community resilience system, the lack of communication and coordination mechanism among participants of the resilience construction, the prevalence of traditional top-down management model for local governments and other stakeholders due to the lack of community-based disaster management concepts among administrative staff, poor engagement of community residents in public health emergency management with predominate role of governments and health institutions, and insufficient emergency response resources supported by local governments to communities and health institutions, with the weight indexes of 0.514, 0.487, 0.467, 0.454, and 0.437, respectively. ConclusionEfficient coordination mechanism among community participants, appropriate community management model, the participation of community residents, and relevant resources support are among the key node issues needing to be concerned in the construction of community resilience system to cope with public health emergency in China.